TP53 codon 72 polymorphism in susceptibility, overall survival, and adjuvant therapy response of gliomas. - Lima-Ramos, V (2013)
TP53 is a key tumor suppressor gene that encodes a transcriptional factor involved in several cellular mechanisms, including growth arrest, DNA repair, and induction of apoptosis. In addition to TP53 gene mutations, a common polymorphism, Arg72Pro, has been involved in the carcinogenesis process. The Pro72 variant has been associated with a slower induction of apoptosis and may influence the risk of cancer development. The role of Arg72Pro polymorphism in glioma susceptibility is poorly characterized. With the objective of analyzing the role of the TP53 Arg72Pro polymorphism in glioma risk, overall survival, and patient therapy response in a Portuguese population, we conducted a retrospective case-control study, including 171 patients with gliomas and 526 cancer-free individuals. The Arg72Pro genotype was assessed by the polymerase chain reaction-restriction fragment length polymorphism technique. No statistically significant differences were observed in the genotypic and allelic frequencies between glioma and control groups, and no statistically significant differences were observed with stratification of gliomas into distinct histological subtypes: astrocytic (n = 115), glioblastoma (n = 75), and oligodendroglial (n = 54) tumors. No significant association was observed between TP53 Arg72Pro and patient overall survival, but Kaplan-Meier analysis of glioma patients harboring the Pro72 allele showed a significantly longer survival with adjuvant therapy. In this first assessment of the role of TP53 Arg72Pro polymorphism in a large series of Portuguese glioma tumors, no association was observed with glioma susceptibility or overall survival, except for patients submitted to adjuvant therapy.